INTRODUCTION OF PLUM VARIETIES IN THE N.V. TSITSIN MAIN BOTANICAL GARDEN OF THE RUSSIAN ACADEMY OF SCIENCES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The data of a long-term study of plum varieties introduced into the collection of theMain Botanical Garden are presented. Varieties that are characterized by high winter hardinessand relatively resistant to diseases in the conditions of the Moscow region have been identified.These varieties are promising for cultivation in the central part of Russia, their description is given.
Keywords: plum, varieties, winter hardiness, introduction test.